Style myślenia o bibliotece doby cyfryzacji. Instytucjonalna identyfikacja biblioteki - Gamrowska, Beata; Mielczarek, Rafał (Biblioteka w chmurze czy chmury nad biblioteką, 2018)
Librar y remains the most important institution of social life. Its position is being set in a dialectical process in which social objectification of library bound to the institutional structure confronts ways that individual think about institution of library. That dialectical process is being shaped by number of factors connected to current civilizational environment – meaning cultural political and economic factors. One of them is Internet. The analysis given in the article is dedicated to the issue of Facebook influence on though style regarding institution of library as well as on the institutional identity of library.